Longitudinal associations of plasma metabolites with persistent fatigue among colorectal cancer survivors up to 2 years after treatment. Issue 2 (2nd September 2022) - van Roekel, Eline H.; Bours, Martijn J. L.; Breukink, Stéphanie O.; Aquarius, Michèl; Keulen, Eric T. P.; Gicquiau, Audrey; Rinaldi, Sabina; Vineis, Paolo; Arts, Ilja C. W.; Gunter, Marc J.; Leitzmann, Michael F.; Scalbert, Augustin; et al.
Abstract: The underlying biological mechanisms causing persistent fatigue complaints after colorectal cancer treatment need further investigation. We investigated longitudinal associations of circulating concentrations of 138 metabolites with total fatigue and subdomains of fatigue between 6 weeks and 2 years after colorectal cancer treatment. Among stage I‐III colorectal cancer survivors (n = 252), blood samples were obtained at 6 weeks, and 6, 12 and 24 months posttreatment. Total fatigue and fatigue subdomains were measured using a validated questionnaire. Tandem mass spectrometry was applied to measure metabolite concentrations (BIOCRATES Absolute IDQ p180 kit). Confounder‐adjusted longitudinal associations were analyzed using linear mixed models, with false discovery rate (FDR) correction. We assessed interindividual (between‐participant differences) and intraindividual longitudinal associations (within‐participant changes over time). In the overall longitudinal analysis, statistically significant associations were observed for 12, 32, 17 and three metabolites with total fatigue and the subscales "fatigue severity, " "reduced motivation" and "reduced activity, " respectively. Specifically, higher concentrations of several amino acids, lysophosphatidylcholines, diacylphosphatidylcholines, acyl‐alkylphosphatidylcholines and sphingomyelins were associated with less fatigue, while higher concentrations of acylcarnitines were associated with more fatigue. For "fatigue severity, " associations appeared mainly driven by intraindividual associations, while for "reduced motivation" stronger interindividual associations were found. We observed longitudinal associations of several metabolites with total fatigue and fatigue subscales, and that intraindividual changes in metabolites over time were associated with fatigue severity. These findings point toward inflammation and an impaired energy metabolism due to mitochondrial dysfunction as underlying mechanisms. Mechanistic studies are necessary to determine whether these metabolites could be targets for intervention. Abstract : What's new? The biological mechanisms underlying persistent fatigue after colorectal cancer treatment remain to be better understood. Here, the authors observed longitudinal associations of several plasma metabolites including amino acids, phospholipids, and acylcarnitines with total fatigue and fatigue subdomains among colorectal cancer survivors. Moreover, within‐individual changes in these metabolites over time were associated with changes in fatigue severity. The findings suggest that low‐grade inflammation and an impaired energy metabolism due to mitochondrial dysfunction may be underlying mechanisms and point to these metabolites as potential targets for interventions to prevent and/or reduce fatigue in colorectal cancer survivors.